Comparative Analysis and Evaluation of Bridge Construction Risk with Multiple Intelligent Algorithms. (15th June 2022) - Wu, Ying; Lu, Pengzhen
Abstract : Bridge collapse in the construction process is one of the most common bridge accidents; we can see the importance of construction to ensure bridge safety. Site construction safety management mainly relies on checklist evaluation, but the evaluation results are often affected by the ability and experience of the evaluator. Using an artificial intelligence algorithm to realize rapid and accurate risk assessment of the bridge construction process is an effective way and development direction to solve the above problems. In view of the uncertain factors in the process of bridge construction, this paper analyzes and classifies the man-made and environmental risk factors that affect the bridge construction stage by using the 4M1E analysis method. Typical artificial intelligence algorithms are used to construct risk assessment models for bridge construction. And the random forest algorithm is used to analyze and verify the construction example of the FIU bridge.